RESONATING STRUGGLES: IDENTIFYING POST-SURGERY SPEECH DISORDERS AMONG CLEFT LIP SUFFERERS AT YAYASAN UMMI ROMLAH - Nastiti, Dian; Muhammad Iqbal Ramdhani (CV. Fahr Publishing, 2024)
This research investigates the speech disorders experienced by individuals who have undergone cleft lip surgery at Yayasan Ummi Romlah. The study aims to identify the specific types of speech disorders resulting from cleft lip sufferer after the surgery, as well as to determine which sounds remain difficult to articulate after the procedure. The research contributes to a deeper understanding of the speech challenges faced by cleft lip and palate patients following surgery. Employing a qualitative method, the study encompasses data collection and analysis techniques. Language utterances from cleft lip patients, primarily obtained through dialogues using the